Kompetensi sosial sebagai kunci kualitas persahabatan remaja: Mengungkap eran attachment dengan orang tua - Hayus, Zuhaimi Santari (Psychological Journal: Science and Practice, 2024)
This study explores the role of social competence in enhancing the quality of adolescent friendships through parental attachment. Adolescence is a crucial developmental stage characterized by significant physical and psychological changes, where peer relationships, particularly friendships, play a vital role in shaping identity. Previous research has highlighted the importance of parental attachment in influencing adolescents’ social interactions and their ability to form meaningful friendships. Social competence, which refers to the ability to navigate social situations effectively, is considered a key mediator between parental attachment and the quality of friendships. This research aims to delve into how social competence mediates the relationship between parental attachment and the quality of adolescent friendships. The study uses quantitative methods with a purposive sampling technique to collect data from 166 adolescents, utilizing various scales to measure parental attachment, social competence, and friendship quality. Results indicate that social competence significantly mediates the relationship between parental attachment and the quality of friendships, confirming its critical role in fostering positive peer relationships during adolescence.